Penyalahgunaan Aplikasi Anonymous Chat terhadap Pola Interaksi Pengguna Anonymous Chat dalam Memicu Prostitusi Online - Fina Widuri; Prilani Prilani; Siti Amanah; Lukman Hakim (UIN Sunan Gunung Djati Bandung, 2023)
The main human need in carrying out life is in terms of interacting with others. In interacting of course humans communicate with each other. However, the interactions that were built through communication in the past and the digital era are now very different. The times have shifted the pattern of interaction to digital media where everyone can access it, especially the anonymous chat application. Therefore, this study aims to discuss the misuse of anonymous chat applications on anonymous chat user interaction patterns that trigger online prostitution. This type of research is included in qualitative research with a phenomenological approach where this research emphasizes the meaning of an action based on individual experience.